2016
DOI: 10.1007/s00521-016-2276-x
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid method based on time–frequency images for classification of alcohol and control EEG signals

Abstract: the-art algorithms manifest that the proposed method outperforms competing algorithms. The experimental outcomes are promising and it can be anticipated that upon its implementation in clinical practice, the proposed scheme will alleviate the onus of the physicians and expedite neurological diseases diagnosis and research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…Bajaj et al [90] introduced a robust method that can automatically identify alcoholic EEG signals based on time-frequency (T-F) image information considering texture image for feature extraction and nonnegative least squares classifier (NNLS) for classification. Kannathal et al [91] developed a feature extraction methodology based on correlation dimension (CD), largest lyapunov exponent (LLE), entropies and Hurst exponent (H) to extract characteristic features from the EEGs of alcoholics.…”
Section: Alcoholism Related-disorders Diagnosismentioning
confidence: 99%
“…Bajaj et al [90] introduced a robust method that can automatically identify alcoholic EEG signals based on time-frequency (T-F) image information considering texture image for feature extraction and nonnegative least squares classifier (NNLS) for classification. Kannathal et al [91] developed a feature extraction methodology based on correlation dimension (CD), largest lyapunov exponent (LLE), entropies and Hurst exponent (H) to extract characteristic features from the EEGs of alcoholics.…”
Section: Alcoholism Related-disorders Diagnosismentioning
confidence: 99%
“…Bernice Projesz et al [24] explain that despite the good results with the thetaband, the beta frequency has become a strong indicator of alcoholism among scientists and medical professionals. However, the results of Wajid Mumtaz et al [10] see a good classifier of alcoholics and non-alcoholics in the thetaband and the Hi-Gamma bands (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Eveline A. de Bruin et al [26] analyze the EEG data of heavy drinking students compared to light drinking students and also comes to the conclusion that the EEG data of heavy drinking students, especially in theta and Gamma band, differ enormously from the EEG data of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Time frequency (TF) images were also used by Bajaj and Pachori (2013) to classify sleep stages. Bajaj et al (2017) also identified alcoholic EEGs based on T-F images. Based on our previous study (Al-Salman et al, 2018) we found that time frequency images coupled with FD yielded promising results in analyzing and detecting sleep spindles in sleep EEG signals.…”
Section: Related Workmentioning
confidence: 99%